(untitled) (INCH : Journal of Infant and Child Healthcare, 2024)
Stunting is a major nutritional problem that occurs due to inadequate intake. One way to prevent stunting is by providing health education to young women. Effective media by increasing health knowledge through educational modules and videos. The research objectives was to analyzing the effectiveness of health education with educational module media and videos through the whatsApp application to increase knowledge about the role of young women in stunting prevention efforts in the Midwifery Department of the Pontianak Health Polytechnic. This type of research with the design used pre and post control design on 82 adolescents using simple random sampling technique. The results is there was a difference in knowledge before and after being given the educational module and video media and there was no significant difference in effectiveness between the educational module and video media on knowledge about stunting prevention.